2012
DOI: 10.1038/gim.2011.73
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequencing of maternal plasma reliably identifies trisomy 18 and trisomy 13 as well as Down syndrome: an international collaborative study

Abstract: Purpose:To determine whether maternal plasma cell–free DNA sequencing can effectively identify trisomy 18 and 13.Methods:Sixty-two pregnancies with trisomy 18 and 12 with trisomy 13 were selected from a cohort of 4,664 pregnancies along with matched euploid controls (including 212 additional Down syndrome and matched controls already reported), and their samples tested using a laboratory-developed, next-generation sequencing test. Interpretation of the results for chromosome 18 and 13 included adjustment for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
485
2
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 465 publications
(509 citation statements)
references
References 23 publications
(41 reference statements)
18
485
2
4
Order By: Relevance
“…Another study then, demonstrated the ability of MPS of maternal plasma to detect fetal trisomy 21 with a near 99% sensitivity and specificity in high-risk pregnancies, defined by maternal age, family history or positive serum and/or sonographic screening tests [7]. The group then published an analysis from the same study demonstrating the detection of trisomy 18 (Edwards syndrome) at 100% sensitivity with a false-positive rate of 0.28%, and trisomy 13 (Patau syndrome) at 91.7% sensitivity with a false-positive rate of 0.97% [28]. The overall detection rate for trisomy 13, 18, and 21 was reported as 98.9% sensitivity with a false-positive rate of 1.4%.…”
Section: Cell-free Dnamentioning
confidence: 99%
“…Another study then, demonstrated the ability of MPS of maternal plasma to detect fetal trisomy 21 with a near 99% sensitivity and specificity in high-risk pregnancies, defined by maternal age, family history or positive serum and/or sonographic screening tests [7]. The group then published an analysis from the same study demonstrating the detection of trisomy 18 (Edwards syndrome) at 100% sensitivity with a false-positive rate of 0.28%, and trisomy 13 (Patau syndrome) at 91.7% sensitivity with a false-positive rate of 0.97% [28]. The overall detection rate for trisomy 13, 18, and 21 was reported as 98.9% sensitivity with a false-positive rate of 1.4%.…”
Section: Cell-free Dnamentioning
confidence: 99%
“…4,[10][11][12] Others have demonstrated a detection rate of over 98% with a false positive rate of less than 0.5%. [13][14][15][16][17][18][19][20] Thus, non-invasive prenatal testing (NIPT) seems to be the most effective screening method in women at high risk 21 and is already available at private laboratories in Brazil for tracking autosomal and sexual aneuploidies.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Using this technology, non-invasive prenatal diagnostic (NIPD) for trisomy 21, 18 and 13 has recently reached the clinical setting by analysing the relative amount of chromosomes in circulating cell-free DNA from maternal plasma. 15,16 However, approaches permitting reliable detection of single-gene mutations or single-nucleotide polymorphisms (SNPs) using cell-free fetal DNA in maternal plasma are still under development. This is considerably more difficult because it concerns fetal genetic changes that differ only slightly from the maternal genome.…”
Section: Introductionmentioning
confidence: 99%